2013
DOI: 10.1038/ismej.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of specific protozoan populations during in situ bioremediation of uranium-contaminated groundwater

Abstract: The importance of bacteria in the anaerobic bioremediation of groundwater polluted with organic and/or metal contaminants is well recognized and in some instances so well understood that modeling of the in situ metabolic activity of the relevant subsurface microorganisms in response to changes in subsurface geochemistry is feasible. However, a potentially significant factor influencing bacterial growth and activity in the subsurface that has not been adequately addressed is protozoan predation of the microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 94 publications
5
25
0
Order By: Relevance
“…Previous studies have shown that these reduced products are formed biologically by dissimilatory Fe(III) and sulfate-reducing bacteria primarily from the genera Geobacter, Desulfobacter and Desulfosporosinus (Anderson et al, 2003;Holmes et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that these reduced products are formed biologically by dissimilatory Fe(III) and sulfate-reducing bacteria primarily from the genera Geobacter, Desulfobacter and Desulfosporosinus (Anderson et al, 2003;Holmes et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, rates of subsurface Geobacter growth were significantly lower than the rates predicted by genome-scale metabolic models (Scheibe et al, 2009;Fang et al, 2011;Lovley et al, 2011;Zhuang et al, 2011). Protozoa grazing on Geobacter species was one possible explanation for this discrepancy (Holmes et al, 2013b), as studies have shown that the specific growth rate of bacteria is higher in the presence of protozoa (Bloem et al, 1988;Verhagen et al, 1995;Strauss and Dodds, 1997;Biagini et al, 1998). In addition to protozoan grazing, it is also likely that phage activity has a substantial impact on bacterial growth in uranium-contaminated aquifers.…”
Section: Introductionmentioning
confidence: 93%
“…Studies at the Rifle site have shown that protozoa become abundant in the groundwater when dissimilatory metal reduction is stimulated by the addition of acetate (64). The increase in protozoan abundance is significant because protozoa can exploit substantial quantities of bacterial biomass production (52), and grazing can significantly stimulate microbial metabolic activity and growth (53,54).…”
Section: Resultsmentioning
confidence: 99%
“…agilis, H. inflata, and B. anathema were chosen as potential G. sulfurreducens grazers because they are related to protozoa previously detected in Geobacter-enriched groundwater (Holmes et al, 2013) and Heteromita strain DH-1 is a protozoan isolate from those groundwaters (D.E. Holmes et al, manuscript in preparation).…”
Section: Studies With Defined Culturesmentioning
confidence: 99%
“…For example, when the growth of Geobacter species in the subsurface was stimulated with the addition of high concentrations of electron donor in the form of acetate, a bloom of protozoa accompanied increases in Geobacter growth and substantially lowered the accumulation of Geobacter biomass below that expected in the absence of protozoan grazing (Holmes et al, 2013). An anode biofilm also represents a substantial enrichment of Geobacteraceae likely to enhance grazing opportunities for protozoa.…”
Section: Introductionmentioning
confidence: 98%